Acculturative Stress Among International Students: A Case of Malaysian Universities - Kee, Daisy Mui Hung; Yyadav, Simran; Ngu, Hui Jie; Rajogoval, Navena A/P; Noor, Nik Nur Syafiqah binti Mohd; Sasitheran, Nathiya A V (AIBPM Publisher, 2022)
Globalization of education is not uncommon in many countries where international education is of major importance to many, including Malaysia. Malaysia has increasingly become a popular destination for study pursues recently due to various attributes such as the wide verbal implementation of English by the locals, affordable accommodation cost, unique traveling experiences, and great opportunities offered at Malaysian higher learning institutions. Globalization of education develops a proactive global learning environment for local students. When international students come to Malaysia, they must adjust rapidly and learn fast, coping academically and socially. This study aims to assess the acculturative stress experienced by international students in Malaysian public universities. The findings indicate that most international students are under moderate cultural pressure, especially cultural changes or shocks, language barriers, and anxiety. These findings have implications for research on stress